2019
DOI: 10.14309/ajg.0000000000000371
|View full text |Cite
|
Sign up to set email alerts
|

One-Hour Esophageal String Test: A Nonendoscopic Minimally Invasive Test That Accurately Detects Disease Activity in Eosinophilic Esophagitis

Abstract: OBJECTIVES:Eosinophilic esophagitis (EoE), a chronic food allergic disease, lacks sensitive and specific peripheral biomarkers. We hypothesized that levels of EoE-related biomarkers captured using a 1-hour minimally invasive Esophageal String Test (EST) would correlate with mucosal eosinophil counts and tissue concentrations of these same biomarkers. We aimed to determine whether a 1-hour EST accurately distinguishes active from inactive EoE or a normal esophagus.METHODS:In a prospective, multisite study, chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 42 publications
0
37
0
Order By: Relevance
“…Providers should be aware of the risk of developing EGIDs, mostly during OIT. When recurrent gastrointestinal symptoms are observed during food AIT or SLIT, the diagnosis of EGIDs should be promptly considered, and patients should undergo GI endoscopy or less invasive diagnostic tools, such as the esophageal string test 76,77 . Fortunately, these complications seem to be reversible by early diagnosis and cessation of OIT and SLIT.…”
Section: Discussionmentioning
confidence: 99%
“…Providers should be aware of the risk of developing EGIDs, mostly during OIT. When recurrent gastrointestinal symptoms are observed during food AIT or SLIT, the diagnosis of EGIDs should be promptly considered, and patients should undergo GI endoscopy or less invasive diagnostic tools, such as the esophageal string test 76,77 . Fortunately, these complications seem to be reversible by early diagnosis and cessation of OIT and SLIT.…”
Section: Discussionmentioning
confidence: 99%
“…The Esophageal String Test (EST) is a minimally invasive technique that utilizes the Enterotest string device which is a gelatin capsule containing a nylon string that is swallowed and later withdrawn through the mouth. EST can detect active EoE inflammation by measuring biomarkers such as eotaxin-3 and major basic protein-1 (8,17,18). Luminal concentrations of eosinophil-associated proteins obtained by EST were found to correlate with esophageal mucosal eosinophilic inflammation (17,18).…”
Section: Diagnosismentioning
confidence: 99%
“…EST can detect active EoE inflammation by measuring biomarkers such as eotaxin-3 and major basic protein-1 (8,17,18). Luminal concentrations of eosinophil-associated proteins obtained by EST were found to correlate with esophageal mucosal eosinophilic inflammation (17,18). A prospective, multisite study evaluating 134 subjects (both pediatric and adult) by Ackerman et al demonstrated that a 1-hour EST accurately distinguishes active vs. inactive EoE in a less invasive and safe manner compared to endoscopic examination with biopsies (18).…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…A drug-eluting string could be swallowed, allowing a sustained release of drug along the entire length of the esophagus, perhaps during an overnight dwell, rather than the usual one-time bolus from a swallowed medication. While the minimally invasive esophageal string test has been used to absorb inflammatory factors related to EoE and characterize disease activity [ 11 , 12 , 13 ], there are no reports of delivering medication to the esophagus in this manner. A recent report outlined how a membrane deployed from a capsule might also target drug delivery to the esophagus.…”
Section: Introductionmentioning
confidence: 99%